2001
DOI: 10.1177/026765830101700406
|View full text |Cite
|
Sign up to set email alerts
|

Analysing interlanguage: how do we know what learners know?

Abstract: In this article, we address the important issue of 'how we know what learners know' based on evidence from second language (L2) learners' spontaneous speech samples gathered longitudinally. We first examine some of the problems involved in the analysis of spontaneous speech, with focus on L2 studies within the generative framework. Next, we revisit the issue of the comparative fallacy in L2 research. We first consider the effects of the comparative fallacy in relation to analyses of interlanguage with a target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…Learning new words and expressions, however, involves learning their syntactic categories and frames, and this is more complex. Beginners have been shown to avoid verbs in early stages (Housen 1997;Lakshmanan and Selinker 2001;Myles in press), relying on the juxtaposition of simple NPs and some PPs to communicate, and I would claim that this is precisely because of the complex relationship verbs entertain with other elements in the sentence. In the case of verbs, not only do learners have to learn a lexical item, but they also have to learn the syntactic representation of its argument structure.…”
Section: L2 Beginnings: the Task Facing Learnersmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning new words and expressions, however, involves learning their syntactic categories and frames, and this is more complex. Beginners have been shown to avoid verbs in early stages (Housen 1997;Lakshmanan and Selinker 2001;Myles in press), relying on the juxtaposition of simple NPs and some PPs to communicate, and I would claim that this is precisely because of the complex relationship verbs entertain with other elements in the sentence. In the case of verbs, not only do learners have to learn a lexical item, but they also have to learn the syntactic representation of its argument structure.…”
Section: L2 Beginnings: the Task Facing Learnersmentioning
confidence: 99%
“…These assumptions are problematic, and the relationship between forms and their linguistic representations in the context of learner language is not as straightforward as this. Researchers have argued that linguistic knowledge can be both under-represented and over-represented in L2 productions (Lakshmanan and Selinker 2001;Lardiere 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This problem, known as the 'comparative fallacy', has recently been cited by Lakshmanan and Selinker (2001) (henceforth L&S) in reference to Lardiere's (1998a) study of tense and pronominal case marking in the L2 English endstate grammar of Patty, a native Chinese speaker who had been living in the USA for 10-18 years, fully immersed in a native English-speaking environment over the eight and a half year period of data collection reported on there.…”
Section: Introductionmentioning
confidence: 99%
“…A more serious criticism was that the morphemes brought together disparate aspects of grammar such as features of the verb phrase (e.g., past regular, past irregular, progressive -ing, third person singular -s) and features of the noun phrase (e.g., plural -s, possessive -s, articles) (Cook 1993). An additional flaw of morpheme studies was found in the level of the accurate suppliance of grammatical morphemes, ranging from 60% to 80% or even 90%, depending on the researcher (Lakshmanan and Selinker 2001). Finally, it has also been claimed that the accurate suppliance of a morpheme in an obligatory context "does not necessarily mean the learner knows its function(s)" (Long and Sato 1984, 260).…”
Section: Morpheme Order Studiesmentioning
confidence: 99%